Revisiting Chlor-Alkali Electrolyzers: from Materials to Devices - Li, Kai; Fan, Qun; Chuai, Hongyuan; Liu, Hai; Zhang, Sheng; Ma, Xinbin (Transactions of Tianjin University, 2021)
As an energy-intensive industry, the chlor-alkali process has caused numerous environmental issues due to heavy electricity consumption and pollution. Chlor-alkali industry has been upgraded from mercury, diaphragm electrolytic cell, to ion exchange membrane (IEM) electrolytic cells. However, several challenges, such as the selectivity of the anodic reaction, sluggish kinetics of alkaline hydrogen evolution, degradation of membranes, the reasonable design of electrolytic cell structure, remain to be addressed. For these reasons, this paper mainly reviews the research progress of the chlor-alkali industry from materials to devices, including hydrogen evolution anode, chlorine evolution cathode, IEM, and electrolytic cell system. Finally, the research directions and prospects in the chlor-alkali industry are proposed for its further improvement.